The Effect of Remote Work on Creativity and Productivity in Creative Agencies - Maulana, Nurzen; Syamsunasir, Syamsunasir (Dinasti International Journal of Management Science, 2025)
Remote work has become a predominant work model in the wake of the COVID-19 pandemic, especially within creative agencies. This literature review examines the impact of remote work on creativity and productivity, highlighting the complexities and nuances that arise in creative environments. By synthesizing findings from various studies, this paper aims to provide insights into how remote work influences the performance of creative professionals and the overall efficacy of creative agencies.